Maternal Loneliness and Technoference During Early Childhood: The Mediating Roles of Nomophobia and Social Media Addiction - Laura Elvira Prino; Donatella Scarzello (European Journal of Investigation in Health, Psychology and Education, 2026)
Maternal technoference has increasingly been recognized as a factor that may compromise mothers’ emotional availability and the quality of mother–child interactions, particularly during early childhood, when responsive caregiving and co-regulation play a pivotal role in children’s development. However, the psychological mechanisms underlying this phenomenon remain poorly understood. Maternal loneliness may represent an important vulnerability factor, although the processes linking loneliness to technoference have yet to be clarified. This study examined whether nomophobia and social media addiction mediate the association between maternal loneliness and technoference. This cross-sectional study included 355 Italian mothers of children aged 0–6 years, who completed measures of loneliness (UCLA 3-item Loneliness Scale), nomophobia (NMP-Q), social media addiction (BSMAS), and technoference (DISRUPT). A parallel mediation model was tested while controlling for maternal age. Loneliness was positively associated with both nomophobia and social media addiction, which were, in turn, positively associated with technoference. Both indirect effects were significant, whereas the direct association between loneliness and technoference was no longer significant. These findings suggest that maternal loneliness may be associated with technoference through its link with nomophobia and social media addiction, highlighting the importance of understanding technoference as a relational phenomenon rather than merely a consequence of technology use.